ANALISIS PENGARUH KETERBUKAAN EKONOMI TERHADAP PERTUMBUHAN EKONOMI (STUDI KASUS: ASEAN TAHUN 2007 – 2017) - Purnomo, Rahmi Nuraini (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2019)
The era of globalization demands an increasingly broad economic openness from every country in the world, both openness in foreign trade (trade openness) and openness to the financial sector. In theory, economic openness benefits all countries involved. The advantages of trade openness include opening up wider market access to achieving higher levels of efficiency and economic competitiveness, as well as opportunities for greater employment. Openness in the financial sector can encourage the entry of foreign capital (capital inflow), and accelerate the occurrence of capital accumulation and technology transfer. This study aims to analyze the effect of economic openness on economic growth in ASEAN (Indonesia, Malaysia, Singapore, Thailand, Philippines, Vietnam, Brunei Darussalam, Cambodia) for the period 2000 - 2017. This study uses panel data regression analysis with a fixed effect approach.               The method in this study uses quantitative research by conducting hypothesis testing. The data used are secondary data from ASEAN countries in 2007-2017 by looking at publications at the World Bank. This study uses panel data, where the panel data is a combination of cross section and time series data. The analytical tool used is panel data regression analysis using the Eviews9 program. Then the best panel data regression model is estimated.               From the stages of analysis carried out, the results of data analysis showed that the results of the panel data estimation selected the best model were Fixed Effext Model (FEM). Hypothesis testing of the results of the Trade Openness (TO) and Foreign Direct Investment (FDI) model have a positive and significant effect on ASEAN Economic Growth (G), while the government expenditure variable (GOV) has no significant positive effect. The inflation variable (INF) has no effect on economic growth.